Teachers’ Challenges and Strategies in Evaluating the Independent Curriculum in Islamic Religious Education: Evidence from SMPN 11 Muaro Jambi - Zeni Musdalifah; Nasir (Universitas Muhammadiyah Surakarta, 2024)
The implementation of the Independent Curriculum requires a paradigm shift in learning evaluation from outcome-oriented assessments to process-based assessments and learning outcomes. In the subject of Islamic Religious Education (PAI), this demand presents its own challenges because the character of PAI not only emphasizes cognitive aspects, but also the formation of attitudes, morals, and spirituality of students. This study aims to examine the problems and strategies of PAI teachers in evaluating the learning of the Independent Curriculum at SMPN 11 Muaro Jambi. The study used a descriptive qualitative approach with the subjects of PAI teachers in grades VII, VIII, and IX. Data were collected through in-depth interviews, learning observations, and documentation, then analyzed using Miles and Huberman's interactive model. The results of the study show that the problems of PAI evaluation are structural and conceptual, including the limitations of official training in the evaluation of the Independent Curriculum, the reduction of PAI learning hours which has an impact on the continuity of assessment, and the difficulty of formalizing attitude and spiritual assessments into accountable evaluation documentation. Responding to these conditions, teachers develop adaptive strategies in the form of continuous observation of attitudes, the use of religious activities as formative assessments, adaptation of teaching tools, and capacity building through independent learning and informal collaboration. This research emphasizes that the evaluation of PAI in the Independent Curriculum is a pedagogical negotiation practice between the demands of curriculum accountability and the character of PAI as value education.